The Impact of Digital Transformation on Educational Outcomes: A Study of Technology Integration in Pakistani Schools - Sain, Zohaib Hassan; Lawal, Uthman Shehu; Karimi, Amir; Lohana, Sonia (Research in Management of Technology and Business, 2024)
The utilisation of digital technologies in the education sector has emerged as a promising solution to address the varied challenges encountered by the educational system in Pakistan. This study investigates the potential influence of digital transformation on educational outcomes, specifically focusing on the impact of technology integration, teacher training, and infrastructure on student engagement and academic performance. This research aims to examine the potential efficacy of digital transformation in enhancing educational standards and reducing regional disparities within Pakistani schools. A mixed-methods approach was adopted, combining quantitative and qualitative data collection techniques. Surveys were administered to 500 students, 100 teachers, and 20 administrators from 50 schools, and academic performance data were collected from school records. Additionally, semi-structured interviews and focus groups were conducted to provide contextual insights. The collected data were analysed using correlation and regression analyses for the quantitative data and thematic analysis for the qualitative data. The research results revealed a significant positive correlation between technology integration and student engagement (r = 0.65, p < 0.01), as well as between teacher training and academic performance (r = 0.48, p < 0.05). The regression analysis indicated that technology integration strongly predicts student engagement (β = 0.52, R² = 0.58, p < 0.01). However, the study highlighted substantial challenges, particularly in rural areas with limited infrastructure and access to digital tools. The study concludes that although digital transformation offers significant potential to enhance educational outcomes, addressing regional disparities is crucial to universalising these benefits nationwide. The research findings have important implications for policymakers. They emphasise the urgent need for targeted interventions to support rural schools and ensure equitable access to digital resources. Furthermore, the findings underscore the importance of continuous teacher training and robust infrastructure to maximise the impact of technology in the educational context.